Management accountants’ personalities and their involvement in business partnering: A job crafting perspective - Dirks, Paula; Tillema, Sandra; Trapp, Rouven (Accounting, Organizations and Society, 2026)
Whereas previous research has largely focused on the top-down establishment of the business partner role, we study bottom-up efforts by individual management accountants to increase their involvement in business partnering and the association of these efforts with their personality. Taking a job crafting perspective, we argue that management accountants may self-initiate changes in their job boundaries toward business partnering. We further argue that management accountants’ job crafting is associated with their plasticity, a disposition for exploration, and the pursuit of new experiences. Drawing on a survey among management accountants employed at a large European bank, we find support for our hypotheses that plasticity has a positive association with job crafting and, through job crafting, with business partnering. Interestingly, this finding particularly holds for management accountants who are not formally required to act as business partners. Our results thus underline that plasticity is a personality trait that can give rise to self-initiated role changes toward business partnering. The results also show that the positive association between job crafting and business partnering is stronger in contexts of tight financial control, which supports our theoretical argument that such contexts provide a greater potential for enhancing the meaningfulness attached to business partnering. Overall, our study highlights that business partnering among management accountants is not inherently linked to their formal job descriptions. Rather, it may emerge as a consequence of self-initiated changes to the job undertaken by individuals possessing appropriate personality traits.